PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP MOTIVASI SERTA DAMPAKNYA PADA KINERJA KADER SURABAYA HEBAT DI KECAMATAN KARANG PILANG - Rika Damayanti; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine the effect of compensation and training on motivation and its impact on the performance of Great Surabaya Cadres in Karang Pilang District. This type of research is quantitative research. The data collection method was by using a questionnaire distributed to 203 respondents. Data analysis consists of descriptive analysis using index values and inferential statistical analysis using SEM AMOS. The results of the research show that there is a positive and significant influence of compensation on performance, there is a positive and significant influence of training on performance, there is a positive and significant influence of compensation on motivation , there is a positive and significant influence of training on motivation, there is a positive and significant influence of motivation on performance, there is a positive and significant influence of compensation on performance through motivation, and there is a positive and significant influence of training on performance through motivation.